The science openness movement in Indonesia: An introduction for re-reading civil society in policy discourse - Cahyo Seftyono; Purwo Santoso; Muhadjir Muhammad Darwin; Agus Heruanto Hadna (Journal of Government and Civil Society, 2020)
Today, civil society is identical to non-government organization (NGO) or Civil Society Organization. Institutional perspective causes the society to always be seen as an organizational entity: as a complete organization with its structure. Consequently, analysis on society will always be nuanced with relation to other institutions: coordination, subordination, opposition, or being attached to each other. This article proposes a new idea on civil society, which is suspected not always working within the institution framework, but instead with a more basic foundation that is ideational thrust. This situation is traceable through Vosviewer tools with Scopus data and Google Scholar database, by selecting one community as a representation. Activities that civil society does are, substantially, ideational discourse from inter-institution actors. Civil society movement is based on ideas, not on institutional administration coordination. This research analyzes Indonesia Open Science Epistemic Community, a community that actively promotes science openness and publication in fulfilling the academic and policy needs. This community transcends institutional division because it involves governmental actors by focusing on ideas. Therefore, this community’s existence could be the new alternative in reading civil society activity.